"I live with terror inside me": Exploring customers' instinctive reactions to terror. (January 2021) - Seger Guttmann, Tali; Gilboa, Shaked; Partouche-Sebban, Judith
Highlights: The present study is the first to test how customers react to reality of terror. The study was conducted in two countries- France and Israel. Analysis identified four main instinctive reactions: emotional, cognitive, behavioral aspects and defensive habits. Findings were similar in two service contexts (hospitality and transportation) and in two different countries (France and Israel). The proximities of time and location impact customers' sense of control, expressed in various coping mechanisms. Abstract: Terrorist attacks occur mostly at public service-oriented sites. Consequently, their victims are likely to be customers. The present study explores how customers instinctively react toward the reality of terror in a matrix of 2 × 2 aspects concerning terror circumstances: temporal proximity (brief or long) and physical proximity (close or remote) from the terror event. In qualitative in-depth interviews, customers from France and Israel were requested to share their instinctive reactions and coping strategies when approaching hospitality (hedonistic) and transportation (utilitarian) services. Participants ( N = 47) comprised customers having a protracted acquaintance with persistent terror threats. The analysis identified differences in reactions, subject to temporal and physical proximities. When terror attacks are physically close, customers' emotions, cognitions, and behaviors undergo modification with time. However, when terror attacks occur at a location remote from the customer, customers' emotions and cognitions, but not their behavior, change with time. These reactions were comparable for the two service contexts. Practical implications were elaborated to enable service establishments (i.e., hospitality and transportation) to design and manage their operations for the short and long term to assist customers in the difficult era of terror.